Design of 0.5 hp induction motor rotor bars with 0.35 mm and 0.50 mm thickness of steel sheets for rotor fabrication - Yanawati Yahya (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2016)
The aim of this research is to design and develop the rotor fabrication of 0.5 Hp 3 phase squirrel cage induction motor with good performances in term of high efficiency, lower losses and economical aspect analysis in term of money and energy saving.